THE CHOICE OF PARAMETERS OF THREE-PIECE TRUCK OF A FREIGHT CAR BY MEANS OF COMPUTER SIMULATION OF ITS DYNAMICS - Kossov, V. S.; Sorochkin, E. M.; Mikhalchenko, H. S.; Pohorielov, D. Yu.; Simonov, V. O. (Science and Transport Progress, 2004)
Some results of designing a three-piece bogie of a freight coach with the help of a precise computer model are presented. The computer model is developed using the Universal Mechanism software. The Hierarchy Analysis Process is applied to choose the rational solution in the parameter space of the model.